First finding of spontaneous infections with Cryptosporidium baileyi and C. meleagridis in the red-legged partridge Alectoris rufa from an aviary in the Czech Republic - Máca, Ondřej; Pavlásek, Ivan (Veterinary parasitology, 2015)
This paper represents the first report of spontaneous infection with Cryptosporidium baileyi and Cryptosporidium meleagridis in the red-legged partridge (Alectoris rufa), as well as the percentage of positive samples and age-associated dynamics of cryptosporidial infections in an aviary in the Czech Republic. The entire infection process was monitored over two semesters (July-December 2012 and 2013) until release of birds for hunting purposes. Coprological examination of 663 pooled fecal samples and 89 post-mortem examinations of red-legged partridges were carried out. Our results indicated that infections with C. baileyi only occurred in 5-7 week-old birds during 2013 (percentage of positivity, 1%) and those with C. meleagridis in 18-22 week (17%) and 17-21 week-old birds (24%) during 2012 and 2013, respectively. Molecular characterization of isolates of C. baileyi and C. meleagridis heat shock protein 70 and actin genes were analyzed in order to support our coprological results. DNA sequence analysis of the 60kDa glycoprotein gene was used to subtype C. meleagridis. Our findings extend the host range for C. baileyi.
Keywords: Poultry Diseases; Gene Expression Regulation; C. baileyi; Galliformes; kryptosporidióza; Česká republika; Cryptosporidiosis; molekulární sekvence - údaje; Amino Acid Sequence; protozoální proteiny; jednonukleotidový polymorfismus; Cryptosporidium meleagridis; HSP70; GP60; Czech Republic; nemoci drůbeže; hostitelská specificita; Animals; Polymorphism, Single Nucleotide; zvířata; regulace genové exprese; sekvence aminokyselin; Actin; Cryptosporidium; Molecular Sequence Data; Protozoan Proteins; Percentage positivity; Host Specificity